Examining the relationship between cognitive emotion regulation strategies and creativity attitude - Momtaz, Tahereh (Kulliyyah of Education, International Islamic University Malaysia, 2015)
This study examines the levels of creativity attitude and cognitive emotion regulation strategies among adolescent students in Iran. It also investigates differences in students' creativity attitude and differences in their use of strategies of cognitive emotion regulation between males and females. Finally, it investigates how cognitive emotion regulation strategies are related to creativity attitude among adolescence. A quantitative approach was adopted for this study. The participants were made up of 340 students between the ages of 16 to 18 years from two public high schools in Ahvaz, center of Khozestan province in Iran. Data were collected by survey questionnaire using the Cognitive Emotion Regulation Questionnaire (CERQ) instrument developed by Garnefski, Kraaij and Spinhoven (2001) and Creativity Attitude Survey (CAS) instrument by Schaefer (1991). The results of the study show that students' level of creativity attitude and Cognitive Emotion Regulation Strategies (CERS) were both moderate. Independent sample t-test revealed that there was no significant difference between gender in CERS and their creativity attitude. In addition, out of the nine dimensions of CERS, rumination and self-blame were found to have negative effect while acceptance and positive refocusing were found to have positive effect on creativity attitude.